Multiple External Seed Dispersers Challenge the Megafaunal Syndrome Anachronism and the Surrogate Ecological Function of Livestock - Blanco, Guillermo; Tella, José L.; Díaz-Luque, José A.; Hiraldo, Fernando (Frontiers in Ecology and Evolution, 2019)
The dispersal of many large-seeded plants is thought to have been handicapped by the extinction of megafauna in the late Pleistocene, and due to the ongoing defaunation of the largest of the extant dispersers. Oversized fruits defined as “megafaunal” provide variable amounts of flesh even though many of them cannot be ingested entirely, nor their seeds defecated, by any extant vertebrate. This apparent mismatch lead to the hypothesis of anachronisms involving extinct megafauna as dispersal-mediated selective agents on fruit traits shaped through endozoochory. It has been suggested that free-ranging livestock partially supply the dispersal functions previously provided by those globally or regionally extinct species. However, there is little knowledge on the role of livestock as a surrogate for megafauna dispersal agents relative to living wild dispersers. Here, we focus on seed dispersal of six palm species (Attalea eichleri, Attalea barreirensis, Attalea speciosa, Attalea princeps, Mauritia flexuosa, Acrocomia totai) with large fruits that conform to the so-called “megafaunal syndrome”. Data on seed dispersal were obtained by observations and camera trapping in the Cerrado, Pantanal and Amazonia biomes in Bolivia and Brazil. Rich communities of wild seed dispersers differing among palm species and study areas were recorded, including rodents, monkeys, canids and a wide variety of birds, especially parrots. Long-distance primary dispersal was mainly conducted by parrots, while multiple species acted as short- and medium-distance secondary dispersers. Among livestock, dispersal was limited to seeds of A. totai and A. princeps moved by several species through stomatochory and endozoochory (mainly regurgitation). These results show that the large seeds can be efficiently dispersed externally by a wide array of present-day vertebrates of variable size but much smaller than extinct megafauna and livestock. A knowledge gap of the natural history of these and other plants with oversized fruits assumed to be maladapted for contemporary dispersal may have been partially favoured by neglecting some key disperser guilds (e.g. parrots) and dispersal mechanisms (e.g. ectoozochory). The evaluation of historic and ongoing defaunation of key external dispersers is advocated to understand the influence of actual (rather than putative) dispersers on contemporary frugivore-plant mutualistic interactions.